Asparagus Polysaccharide Suppresses the Migration, Invasion, and Angiogenesis of Hepatocellular Carcinoma Cells Partly by Targeting the HIF-1α/VEGF Signalling Pathway In Vitro. (26th May 2019) - Cheng, Wei; Cheng, Ziwei; Xing, Dongwei; Zhang, Minguang
Abstract : Hypoxia-inducible factor-1 α (HIF-1 α ) plays a key role by triggering the transcriptional activation of a number of genes involved in migration, invasion, and angiogenesis in hepatocellular carcinoma (HCC). Thus, suppressing tumour growth by targeting the HIF-1 α /VEGF signalling pathway represents a promising strategy for the treatment of HCC. In our previous studies, we found that asparagus polysaccharide (ASP) suppressed the proliferation and promoted the apoptosis of HCC cells both in vivo and in vitro. To further explore the potential mechanisms of the antitumor effects of ASP in HCC, we investigated effects of ASP on the migration, invasion, and angiogenesis of HCC cells (SK-Hep1 and Hep-3B) using an in vitro experimental model. First, we found that ASP effectively suppressed the proliferation of the SK-Hep1 and Hep-3B cells but did not cause significant cytotoxicity in normal liver cells (L-O2). Then, we found that ASP inhibited the migration and invasion of the SK-Hep1 and Hep-3B cells and HCC cells-induced angiogenesis of human umbilical vein endothelial cells in a concentration-dependent manner. Mechanistic studies revealed that the inhibition of migration, invasion, and angiogenesis by ASP in the SK-Hep1 and Hep-3B cells might occur via the downregulation of HIF-1 α /VEGF signalling pathway. Finally, our results also showed that the inhibition of HIF-1 α by ASP may be mediated through the downregulation of the phosphorylation levels of AKT, mTOR, and ERK. In conclusion, our results suggest that ASP suppresses the migration, invasion, and angiogenesis of HCC cells partly via inhibiting the HIF-1 α /VEGF signalling pathway.